A core-shell structure composite antibacterial agent and a preparation method thereof

CN117598322BActive Publication Date: 2026-10-16LIMING VOCATIONAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311581612.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2026-10-16
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

[0002]壳聚糖季铵盐具有优良的抗菌性能,但是壳聚糖季铵盐的热稳定性不良,难以经过熔融共混添加到塑料基材中

Benefits of technology

[0030] First, considering the compatibility of the composite materials, the selected chitosan quaternary ammonium salt with long-chain alkyl groups exhibits amphiphilicity (both hydrophilic and lipophilic); the organic modification of nano-zinc oxide also facilitates dispersion in the moderately cross-linked lipophilic shell. Therefore, the interfacial compatibility of chitosan quaternary ammonium salt, organic nano-zinc oxide, and polymer shell is better, contributing to the stability of the core-shell structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004568600010000061
    Figure BDA0004568600010000061
  • Figure BDA0004568600010000071
    Figure BDA0004568600010000071
  • Figure BDA0004568600010000072
    Figure BDA0004568600010000072
Patent Text Reader

Abstract

The application discloses a kind of composite antibacterial agent of core-shell structure, including organic nanometer zinc oxide 3-10 parts, oily solvent 50-200 parts, surfactant 5-20 parts, chitosan quaternary ammonium salt solution 5-30 parts, dispersant aqueous solution 500-1500 parts, A monomer 5-15 parts, B monomer 0.1-0.5 parts and initiator 0.025-0.30 parts.The application further discloses a kind of preparation method of composite antibacterial agent of core-shell structure, using above-mentioned raw materials, construct special emulsion system, with chitosan quaternary ammonium salt as core layer, form shell layer by monomer polymerization reaction, finally generate composite antibacterial agent of core-shell structure.The application is constructed by emulsion system, so that organic nanometer zinc oxide and moderate crosslinking polymer are as shell layer to chitosan quaternary ammonium salt is wrapped.The chitosan quaternary ammonium salt selected by the application has amphiphilic, can improve the stability of core-shell structure.Organic nanometer zinc oxide lipophilicity and lipophilic shell layer have better compatibility, can improve the thermal stability of composite antibacterial agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of composite antibacterial agents, and in particular to a core-shell structured composite antibacterial agent and its preparation method. Background Technology

[0002] Chitosan quaternary ammonium salts possess excellent antibacterial properties; however, their poor thermal stability makes them difficult to add to plastic substrates via melt blending. This thermal stability limits their application in antibacterial materials.

[0003] Common chitosan quaternary ammonium salts are mainly modified with 2,3-epoxypropyltrimethylammonium chloride. The resulting chitosan quaternary ammonium salts are usually only highly hydrophilic, which is not conducive to their dispersion in oleophilic plastics or rubber matrices.

[0004] In view of this, the inventor of this case conducted in-depth research, which led to the creation of this case. Summary of the Invention

[0005] The purpose of this invention is to provide a core-shell structured composite antibacterial agent with good thermal stability.

[0006] Another objective of this invention is to provide a method for preparing a core-shell structured composite antibacterial agent with good thermal stability.

[0007] To achieve the above objectives, the technical solution of the present invention is as follows:

[0008] A core-shell structured composite antibacterial agent is prepared according to the following parts by weight: 3-10 parts of organic nano zinc oxide, 50-200 parts of oily solvent, 5-20 parts of surfactant, 5-30 parts of chitosan quaternary ammonium salt solution, 500-1500 parts of dispersant aqueous solution, 5-15 parts of monomer A, 0.1-0.5 parts of monomer B, and 0.025-0.30 parts of initiator;

[0009] The heat resistance temperature of the composite antibacterial agent is 270-290℃;

[0010] The chitosan quaternary ammonium salt is N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt and / or N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt;

[0011] The monomer A is one or a combination of several of the following: styrene monomers, acrylate monomers, methacrylate monomers, vinyl ester monomers, and acrylic monomers.

[0012] The styrene monomers include one or more combinations of styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 2,6-dimethylstyrene, 2-chlorostyrene, 2-bromostyrene, 4-bromostyrene, and p-tert-butylstyrene; the acrylate monomers include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, lauryl acrylate, and 2-ethylhexyl acrylate; the methacrylate monomers include methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate; the vinyl ester monomers include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl stearate, vinyl lauryl acrylate, and vinyl myristate; the acrylic monomers include acrylic acid and methacrylic acid.

[0013] The monomer B used is one or more of divinylbenzene, pentaerythritol triallyl ether and N,N-methylenebisacrylamide;

[0014] The preparation method of the organic nano zinc oxide is as follows: nano zinc oxide is placed in an ethanol aqueous solution with an ethanol mass fraction of 40-60%, and ultrasonically crushed for 0.5-1 h. Under a water bath at 500-1500 rpm and 40-80℃, a silane coupling agent ethanol solution with a mass fraction of 3-5% is uniformly added dropwise and the reaction is maintained for 1-4 h. After the reaction is completed, the mixture is cooled to room temperature, washed with anhydrous ethanol, the solid is separated, and obtained by vacuum drying.

[0015] The structure of the composite antibacterial agent includes a core layer and a shell layer. The shell layer is formed by polymerizing a mixture of monomers A and B to form a cross-linked copolymer. The alkyl long chains of both the organic nano zinc oxide and the shell cross-linked polymer are lipophilic. The organic nano zinc oxide is dispersed into the shell layer and immobilized in situ. The chitosan quaternary ammonium salt is the core layer, and the lipophilic alkyl long chains of the chitosan quaternary ammonium salt form a physical entanglement with the shell layer.

[0016] After adopting the above technical solution, the composite antibacterial agent with the core-shell structure of the present invention has the following beneficial effects: The structure of the composite antibacterial agent includes a core layer and a shell layer. The shell layer is formed by polymerizing a mixture of monomer A and monomer B to form a cross-linked copolymer. Both the organic nano zinc oxide and the alkyl long chains of the cross-linked polymer in the shell layer are lipophilic and have good compatibility, which is conducive to the dispersion of organic nano zinc oxide into the shell layer and its in-situ immobilization. The core layer is composed of chitosan quaternary ammonium salt. The lipophilic alkyl long chains of chitosan quaternary ammonium salt have similar polarity to the lipophilic ends of the shell layer. The lipophilic alkyl long chain segments are more easily dispersed into the shell layer to form physical entanglement, which is beneficial to improving the stability of the core-shell structure.

[0017] A method for preparing the aforementioned core-shell structured composite antibacterial agent includes the following steps:

[0018] Step 1: Add surfactant to oily solvent in proportion, water bath temperature is 40-80℃, stirring speed is 500-2000 rpm, stir until surfactant is fully dissolved or dispersed to obtain solvent;

[0019] Step 2: Add the chitosan quaternary ammonium salt aqueous solution and organic nano zinc oxide to the oily solvent in Step 1, stir at 500-2000 rpm and water bath at 40-80℃ to fully emulsify the mixture and form a water-in-oil emulsion.

[0020] Step 3: Transfer the water emulsion obtained in Step 2 to the dispersant aqueous solution, stir at 500-1000 rpm, and water bath at 40-80℃ to form an oil-in-water emulsion.

[0021] Step 4: Keep the stirring speed and temperature constant, mix monomer A and monomer B evenly to form a monomer mixture, and add the monomer mixture dropwise to the emulsion obtained in step 3 at a rate of 0.1-0.2 mL / min. Start timing from the first drop of monomer mixture added. Add the initiator after 20-30 minutes and maintain the reaction for 1-5 hours. After the reaction is completed, cool the emulsion to below 40°C.

[0022] Step 5: Add a demulsifier to the emulsion in step 4 to precipitate a solid. After washing the solid with ethanol, deionized water, etc., dry it in a vacuum oven at low temperature or freeze-dry it to obtain a composite antibacterial agent with chitosan quaternary ammonium salt as the core layer and organic nano zinc oxide and polymer as the shell layer.

[0023] Furthermore, the degree of substitution of the chitosan quaternary ammonium salt is 40-90%, and the relative molecular mass is 50,000-800,000.

[0024] Furthermore, the solid content of the chitosan quaternary ammonium salt solution is 1-10% by weight.

[0025] Furthermore, the oily solvent is liquid paraffin and / or petroleum ether.

[0026] Furthermore, the surfactant is one or more of Span-40, Span-60, Span-80, calcium stearate, and magnesium stearate.

[0027] Furthermore, the dispersant aqueous solution is a polyvinyl alcohol aqueous solution or a polyvinylpyrrolidone aqueous solution, and the mass fraction of the dispersant is 1-3%.

[0028] Furthermore, the initiator is one or a combination of two of the following: ammonium persulfate, potassium persulfate, sodium bisulfite, sodium sulfite, tetramethylethylenediamine, benzoyl peroxide, dodecyl peroxide, dicumyl peroxide, and di-tert-butyl peroxide.

[0029] By adopting the above technical solution, the preparation method of the core-shell structured composite antibacterial agent of the present invention has the following beneficial effects:

[0030] First, considering the compatibility of the composite materials, the selected chitosan quaternary ammonium salt with long-chain alkyl groups exhibits amphiphilicity (both hydrophilic and lipophilic); the organic modification of nano-zinc oxide also facilitates dispersion in the moderately cross-linked lipophilic shell. Therefore, the interfacial compatibility of chitosan quaternary ammonium salt, organic nano-zinc oxide, and polymer shell is better, contributing to the stability of the core-shell structure.

[0031] Secondly, from the perspective of core-shell structure design, the cross-linked polymer layer of the shell can immobilize organic nano-zinc oxide. Compared with the structure design that only uses inorganic particles to cover the shell, the core-shell structure of this invention can reduce the thermal degradation of chitosan quaternary ammonium salt, improve the thermal stability of composite materials, and broaden the application of composite antibacterial agents.

[0032] Furthermore, regarding the antibacterial properties of the antibacterial agent, both chitosan quaternary ammonium salt and nano-zinc oxide possess antibacterial efficacy. Organically modified nano-zinc oxide is less prone to aggregation, making it more suitable for application. The chitosan quaternary ammonium salt and organically modified nano-zinc oxide of this invention exhibit synergistic antibacterial effects. The composite antibacterial agent of this invention demonstrates an antibacterial rate of 97.9%–99.9% against *Escherichia coli* and 98.0%–99.9% against *Staphylococcus aureus*. Under the same conditions, N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt and N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt exhibit antibacterial rates of 80.2%–85.6% against *Escherichia coli* and 77.6%–80.2% against *Staphylococcus aureus*. Under the same conditions, organically modified nano-zinc oxide demonstrates an antibacterial rate of 86.2% against *Escherichia coli* and 87.5% against *Staphylococcus aureus*. Detailed Implementation

[0033] To further explain the technical solution of the present invention, the present invention will be described in detail below through specific embodiments.

[0034] Example 1

[0035] This invention discloses a core-shell structured composite antibacterial agent, the raw material ratio (parts by weight) of which is as follows: 3 parts organic nano zinc oxide, 200 parts liquid paraffin, 12.5 parts Span-80 surfactant, 7.5 parts calcium stearate, 25 parts N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt solution, 1500 parts polyvinyl alcohol aqueous solution, 12 parts styrene, 3 parts methacrylic acid, 0.16 parts divinylbenzene, 0.04 parts N,N-methylenebisacrylamide, 0.12 parts ammonium persulfate, and 0.10 parts sodium bisulfite.

[0036] Specifically, the relative molecular mass of N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt is 200,000, the degree of substitution is 80%, and the solid content of its solution is 8%.

[0037] The solid content of the polyvinyl alcohol aqueous solution is 1%.

[0038] In this invention, in addition to the aforementioned N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt, N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt can also be used. The chemical structural formulas of N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt and N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt are as follows:

[0039]

[0040] The preparation method of the organic nano zinc oxide used in this invention (including Examples 1-4) is as follows: Nano zinc oxide is placed in an ethanol-water solution (ethanol mass fraction 50%), ultrasonically crushed for 0.5 h, and then slowly and uniformly added dropwise at 800 rpm and a 50°C water bath to a 3% (mass fraction) silane coupling agent (KH570 is specifically used as an example below) ethanol solution. The reaction is maintained for 2 h. After the reaction is completed, the mixture is cooled to room temperature, washed with anhydrous ethanol, and the solid is separated. After vacuum drying, the organic nano zinc oxide is obtained. The reaction equation is as follows: Step 1. Hydrolysis of the silane coupling agent (using KH570 as an example)

[0041]

[0042] Step 2. Zinc oxide coupling modification

[0043]

[0044] The present invention discloses a method for preparing a core-shell structured composite antibacterial agent, comprising the following steps:

[0045] Step 1: Add Span-80 and calcium stearate to liquid paraffin in the above proportion. The water bath temperature is 50°C and the stirring speed is 1000 rpm. Stir until the surfactant is fully dissolved or dispersed to obtain the solvent.

[0046] Step 2: Add the aqueous solution of N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt and the organic nano zinc oxide to the solvent obtained in Step 1, respectively. Stir at 1000 rpm and water bath at 50°C to fully emulsify the mixture and form a water-in-oil emulsion.

[0047] Step 3: Transfer the water-in-oil emulsion obtained in Step 2 to a polyvinyl alcohol aqueous solution, stir at 800 rpm, and keep the water bath temperature at 60°C to form a water-in-oil-in-water emulsion.

[0048] Step 4: Keeping the stirring speed and temperature of Step 3 constant, mix styrene, methacrylic acid, divinylbenzene and N,N-methylenebisacrylamide evenly to form a monomer mixture. Add the monomer mixture dropwise to the emulsion obtained in Step 3 at a rate of 0.2 mL / min. Start timing from the first drop of monomer mixture added. After 30 min, add ammonium persulfate and sodium bisulfite and maintain the reaction for 4 h. After the reaction is completed, cool the emulsion after the reaction to below 40°C.

[0049] In this embodiment, the shell crosslinking polymerization reaction equation is as follows:

[0050]

[0051] Where n = n1 + n2 + n3 + n4 + n5 + n6, x = x1 + x2 + x3 + x4 + x5 + x6; and n, m, x and y are all positive integers.

[0052] The interaction mechanism between the shell cross-linked polymer and the organic nano-zinc oxide is as follows:

[0053] Note: Represents organic nano zinc oxide, symbol express

[0054] Step 5: Add a demulsifier to the emulsion in step 4 to precipitate a solid. After washing the solid with ethanol, deionized water, etc., dry it in a vacuum oven at low temperature or freeze-dry it to obtain a composite antibacterial agent with chitosan quaternary ammonium salt as the core layer and organic nano zinc oxide and polymer as the shell layer.

[0055] The core-shell structure of the composite antibacterial agent is shown below:

[0056]

[0057] Note 2: In structural formulas, symbols This refers to the N-hexadecyl-N,N-dimethylchitosan quaternary ammonium salt in this embodiment.

[0058] Note 3: In structural formulas, symbols This indicates the organic nano zinc oxide in this embodiment.

[0059] The core-shell composite antibacterial agent prepared in this invention was tested using an oscillation method. The antibacterial agent showed an antibacterial rate of 97.9% against *Escherichia coli* and 98.0% against *Staphylococcus aureus*. Under the same conditions, N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt showed an antibacterial rate of 85.6% against *Escherichia coli* and 80.2% against *Staphylococcus aureus*. Under the same conditions, organic nano-zinc oxide showed an antibacterial rate of 86.2% against *Escherichia coli* and 87.5% against *Staphylococcus aureus*. The comparison of antibacterial rate data indicates that the core-shell composite antibacterial agent prepared in this embodiment has a better antibacterial effect than using a single antibacterial agent under the same conditions.

[0060] The core-shell composite antibacterial agent prepared by this invention begins to lose thermal weight at 270℃, reaches its maximum rate of thermal weight loss at 312℃, and terminates thermal decomposition at approximately 335℃. The unmodified N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt begins to lose thermal weight at 221℃, reaches its maximum rate of thermal weight loss at 297℃, and terminates thermal decomposition at 302℃. The comparison of thermal performance data shows that, compared to a single chitosan quaternary ammonium salt, the core-shell composite antibacterial agent of this invention (i.e., the modified chitosan quaternary ammonium salt) improves the overall thermal stability of the antibacterial agent.

[0061] This invention discloses a method for preparing a core-shell structured composite antibacterial agent. Through the construction of an emulsion system, organic nano-zinc oxide and a moderately cross-linked polymer are used as the shell layer to encapsulate a chitosan quaternary ammonium salt. The chitosan quaternary ammonium salt selected in this invention is N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt, N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt, etc., which possess both lipophilic long-chain alkyl groups and hydrophilic quaternary ammonium salt groups, exhibiting amphiphilicity. The lipophilic long-chain alkyl groups are more similar in polarity to the lipophilic shell material, and the lipophilic alkyl long-chain segments are more easily dispersed in the shell layer, forming physical entanglement, thereby improving the stability of the core-shell structure. Furthermore, the lipophilicity of the organic nano-zinc oxide, compared to unmodified nano-zinc oxide, results in better compatibility with the lipophilic polymer layer and also improves the thermal stability of the composite antibacterial agent. Simultaneously, the organic nano-zinc oxide possesses certain antibacterial properties, enhancing the antibacterial efficacy of the composite antibacterial agent.

[0062] Example 2:

[0063] This invention discloses a core-shell structured composite antibacterial agent, the raw material ratio (parts by weight) of which is as follows: 5 parts organic nano zinc oxide, 120 parts liquid paraffin, 15 parts Span-80 surfactant, 5 parts calcium stearate, 18 parts N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt solution, 1000 parts polyvinyl alcohol aqueous solution, 7.2 parts styrene, 2.4 parts methyl methacrylate, 2.4 parts acrylic acid, 0.12 parts divinylbenzene, 0.04 parts N,N-methylenebisacrylamide, 0.1 parts ammonium persulfate, and 0.08 parts sodium bisulfite.

[0064] Specifically, the relative molecular mass of N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt is 300,000, the degree of substitution is 70%, and the solid content of its solution is 5%.

[0065] The solid content of the polyvinyl alcohol aqueous solution is 2%;

[0066] The present invention discloses a method for preparing a core-shell structured composite antibacterial agent, comprising the following steps:

[0067] Step 1: Add Span-80 and calcium stearate to liquid paraffin in the above proportion. The water bath temperature is 60°C and the stirring speed is 1000 rpm. Stir until the surfactant is fully dissolved or dispersed to obtain the solvent.

[0068] Step 2: Add the aqueous solution of N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt and the organic nano zinc oxide to the solvent obtained in Step 1, respectively. Stir at 1000 rpm and water bath at 60°C to fully emulsify the mixture and form a water-in-oil emulsion.

[0069] Step 3: Transfer the water-in-oil emulsion obtained in Step 2 to a polyvinyl alcohol aqueous solution, stir at 800 rpm, and keep the water bath temperature at 70°C to form a water-in-oil-in-water emulsion.

[0070] Step 4: Keeping the stirring speed and temperature of Step 3 constant, mix styrene, methyl methacrylate, acrylic acid, divinylbenzene and N,N-methylenebisacrylamide evenly to form a monomer mixture. Add the monomer mixture dropwise to the emulsion obtained in Step 3 at a rate of 0.15 mL / min, starting the timer from the first drop of monomer mixture added. After 30 min, add ammonium persulfate and sodium bisulfite, and maintain the reaction (shell crosslinking polymerization reaction) for 4 h. After the reaction is completed, cool the emulsion after the reaction to below 40°C.

[0071] Step 5: Add a demulsifier to the emulsion in step 4 to precipitate a solid. After washing the solid with ethanol, deionized water, etc., dry it in a vacuum oven at low temperature or freeze-dry it to obtain a composite antibacterial agent with chitosan quaternary ammonium salt as the core layer and organic nano zinc oxide and polymer as the shell layer.

[0072] The core-shell composite antibacterial agent prepared in this invention was tested for performance using an oscillation method. The antibacterial agent showed an antibacterial rate of 98.1% against *Escherichia coli* and 98.3% against *Staphylococcus aureus*. Under the same conditions, N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt showed an antibacterial rate of 85.6% against *Escherichia coli* and 80.2% against *Staphylococcus aureus*. Under the same conditions, organic nano-zinc oxide showed an antibacterial rate of 86.2% against *Escherichia coli* and 87.5% against *Staphylococcus aureus*. The comparison of antibacterial rate data indicates that the core-shell composite antibacterial agent prepared in this embodiment has a better antibacterial effect than using a single antibacterial agent under the same conditions.

[0073] The core-shell structured composite antibacterial agent prepared in this invention begins to lose thermal weight at 275℃, reaches its maximum rate of thermal weight loss at 324℃, and terminates thermal decomposition at approximately 344℃. The unmodified N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt begins to lose thermal weight at 221℃, reaches its maximum rate of thermal weight loss at 297℃, and terminates thermal decomposition at 302℃. The comparison of thermal performance data shows that, compared to a single chitosan quaternary ammonium salt, the core-shell structure improves the overall thermal stability of the antibacterial agent.

[0074] Example 3:

[0075] This invention discloses a core-shell structured composite antibacterial agent, the raw material ratio (parts by weight) of which is as follows: 8 parts organic nano zinc oxide, 150 parts petroleum ether, 5 parts Span-60 surfactant, 2 parts magnesium stearate, 10 parts N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt solution, 1200 parts polyvinylpyrrolidone aqueous solution, 3 parts methyl methacrylate, 1 part vinyl acetate, 1 part methacrylic acid, 0.08 parts divinylbenzene, 0.02 parts N,N-methylenebisacrylamide, and 0.025 parts benzoyl peroxide.

[0076] Specifically, the relative molecular mass of N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt is 400,000, the degree of substitution is 90%, and the solid content of its solution is 10%.

[0077] The solid content of the polyvinyl alcohol aqueous solution is 1%.

[0078] The present invention discloses a method for preparing a core-shell structured composite antibacterial agent, comprising the following steps:

[0079] Step 1: Add Span-60 and magnesium stearate to petroleum ether in the above proportion. The water bath temperature is 40°C and the stirring speed is 1000 rpm. Stir until the surfactant is fully dissolved or dispersed to obtain the solvent.

[0080] Step 2: Add the chitosan quaternary ammonium salt aqueous solution and the organic nano zinc oxide to the solvent obtained in Step 1, respectively. Stir at 1200 rpm and water bath at 50°C to fully emulsify the mixture and form a water-in-oil emulsion.

[0081] Step 3: Transfer the water-in-oil emulsion obtained in Step 2 to a polyvinylpyrrolidone aqueous solution, stir at 800 rpm, and water bath at 60°C to form a water-in-oil-in-water emulsion.

[0082] Step 4: Keeping the stirring speed and temperature of Step 3 constant, mix methyl methacrylate, vinyl acetate, methacrylic acid, divinylbenzene and N,N-methylenebisacrylamide evenly to form a monomer mixture. Add the monomer mixture dropwise to the emulsion obtained in Step 3 at a rate of 0.1 mL / min. Start timing from the first drop of monomer mixture added. After 30 min, add benzoyl peroxide and maintain the reaction for 5 h. After the reaction is completed, cool the emulsion after the reaction to below 40°C.

[0083] Step 5: Add a demulsifier to the emulsion in step 4 to precipitate a solid. After washing the solid with ethanol, deionized water, etc., dry it in a vacuum oven at low temperature or freeze-dry it to obtain a composite antibacterial agent with chitosan quaternary ammonium salt as the core layer and organic nano zinc oxide and polymer as the shell layer.

[0084] The core-shell composite antibacterial agent prepared in this invention was tested for performance using an oscillation method. The antibacterial agent showed an antibacterial rate of 99.0% against *Escherichia coli* and 99.5% against *Staphylococcus aureus*. Under the same conditions, N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt showed an antibacterial rate of 85.6% against *Escherichia coli* and 80.2% against *Staphylococcus aureus*. Under the same conditions, organic nano-zinc oxide showed an antibacterial rate of 86.2% against *Escherichia coli* and 87.5% against *Staphylococcus aureus*. The comparison of antibacterial rate data indicates that the core-shell composite antibacterial agent prepared in this embodiment has a better antibacterial effect than using a single antibacterial agent under the same conditions.

[0085] The core-shell composite antibacterial agent prepared by this invention begins to lose thermal weight at 283℃, reaches its maximum rate of thermal weight loss at 330℃, and terminates thermal decomposition at approximately 352℃. The unmodified N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt begins to lose thermal weight at 221℃, reaches its maximum rate of thermal weight loss at 297℃, and terminates thermal decomposition at 302℃. The comparison of thermal performance data shows that, compared to a single chitosan quaternary ammonium salt, the core-shell composite antibacterial agent of this invention (i.e., the modified chitosan quaternary ammonium salt) improves the overall thermal stability of the antibacterial agent.

[0086] Example 4:

[0087] This invention discloses a core-shell structured composite antibacterial agent, the raw material ratio (parts by weight) of which is as follows: 10 parts organic nano zinc oxide, 200 parts liquid paraffin, 9.6 parts Span-40 surfactant, 2.4 parts calcium stearate, 10 parts N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt solution, 1300 parts polyvinyl alcohol aqueous solution, 4 parts methyl methacrylate, 2 parts butyl acrylate, 2 parts vinyl acetate, 1 part acrylic acid, 0.12 parts pentaerythritol triallyl ether, 0.02 parts N,N-methylenebisacrylamide, 0.05 parts ammonium persulfate, and 0.02 parts sodium bisulfite.

[0088] Specifically, the relative molecular mass of N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt is 100,000, the degree of substitution is 60%, and the solid content of its solution is 6%.

[0089] The solid content of the polyvinyl alcohol aqueous solution is 2%;

[0090] The present invention discloses a method for preparing a core-shell structured composite antibacterial agent, comprising the following steps:

[0091] Step 1: Add Span-40 and calcium stearate to liquid paraffin in the above proportion. The water bath temperature is 40°C and the stirring speed is 800 rpm. Stir until the surfactant is fully dissolved or dispersed to obtain the solvent.

[0092] Step 2: Add the aqueous solution of N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt and the organic nano zinc oxide to the solvent obtained in Step 1, respectively. Stir at 1000 rpm and water bath at 50°C to fully emulsify the mixture and form a water-in-oil emulsion.

[0093] Step 3: Transfer the water-in-oil emulsion obtained in Step 2 to a polyvinyl alcohol aqueous solution, stir at 1000 rpm, and water bath at 60°C to form a water-in-oil-in-water emulsion.

[0094] Step 4: Keeping the stirring speed and temperature of Step 3 constant, mix methyl methacrylate, butyl acrylate, vinyl acetate, acrylic acid, pentaerythritol triallyl ether, and N,N-methylenebisacrylamide evenly to form a monomer mixture. Add the monomer mixture dropwise to the emulsion obtained in Step 3 at a rate of 0.15 mL / min, starting the timer from the first drop of monomer mixture added. After 30 min, add ammonium persulfate and sodium bisulfite, and maintain the reaction for 4.5 h. After the reaction is completed, cool the emulsion after the reaction to below 40°C.

[0095] Step 5: Add a demulsifier to the emulsion in step 4 to precipitate a solid. After washing the solid with ethanol, deionized water, etc., dry it in a vacuum oven at low temperature or freeze-dry it to obtain a composite antibacterial agent with chitosan quaternary ammonium salt as the core layer and organic nano zinc oxide and polymer as the shell layer.

[0096] The core-shell composite antibacterial agent prepared in this invention was tested for performance using an oscillation method. The antibacterial agent showed an antibacterial rate greater than 99.9% against *Escherichia coli* and greater than 99.9% against *Staphylococcus aureus*. Under the same conditions, N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt showed an antibacterial rate of 80.2% against *Escherichia coli* and 77.6% against *Staphylococcus aureus*. Under the same conditions, organic nano-zinc oxide showed an antibacterial rate of 86.2% against *Escherichia coli* and 87.5% against *Staphylococcus aureus*. The comparison of antibacterial rate data indicates that the core-shell composite antibacterial agent prepared in this embodiment has a better antibacterial effect than using a single antibacterial agent under the same conditions.

[0097] The core-shell structured composite antibacterial agent prepared by this invention begins to lose thermal weight at 290℃, reaches its maximum rate of thermal weight loss at 342℃, and terminates thermal decomposition at approximately 361℃. The unmodified N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt begins to lose thermal weight at 225℃, reaches its maximum rate of thermal weight loss at 300℃, and terminates thermal decomposition at 305℃. The comparison of thermal performance data shows that, compared to a single chitosan quaternary ammonium salt, the core-shell structure improves the overall thermal stability of the antibacterial agent.

[0098] The above embodiments are not intended to limit the composite antibacterial agent and its preparation method of the present invention. Any appropriate changes or modifications made by those skilled in the art should be considered as not departing from the patent scope of the present invention.

Claims

1. A core-shell structured composite antibacterial agent, characterized in that: It is prepared according to the following parts by weight: 3-10 parts of organic nano zinc oxide, 50-200 parts of oily solvent, 5-20 parts of surfactant, 5-30 parts of chitosan quaternary ammonium salt solution, 500-1500 parts of dispersant aqueous solution, 5-15 parts of monomer A, 0.1-0.5 parts of monomer B and 0.025-0.30 parts of initiator; The heat resistance temperature of the composite antibacterial agent is 270-290℃; The chitosan quaternary ammonium salt is N-hexadecyl-N,N-dimethyl chitosan quaternary ammonium salt and / or N-octadecyl-N,N-dimethyl chitosan quaternary ammonium salt; The monomer A is one or a combination of several of the following: styrene monomers, acrylate monomers, methacrylate monomers, vinyl ester monomers, and acrylic monomers. The styrene monomers include one or more combinations of styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 2,6-dimethylstyrene, 2-chlorostyrene, 2-bromostyrene, 4-bromostyrene, and p-tert-butylstyrene; the acrylate monomers include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, lauryl acrylate, and 2-ethylhexyl acrylate; the methacrylate monomers include methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate; the vinyl ester monomers include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl stearate, vinyl lauryl acrylate, and vinyl myristate; the acrylic monomers include acrylic acid and methacrylic acid. The monomer B used is one or more of divinylbenzene, pentaerythritol triallyl ether and N,N-methylenebisacrylamide; The preparation method of the organic nano zinc oxide is as follows: nano zinc oxide is placed in an ethanol aqueous solution with an ethanol mass fraction of 40-60%, and ultrasonically crushed for 0.5-1 h. Then, a silane coupling agent ethanol solution with a mass fraction of 3-5% is uniformly added dropwise at 500-1500 rpm and 40-80 ℃ in a water bath. The reaction is maintained for 1-4 h. After the reaction is completed, the mixture is cooled to room temperature, washed with anhydrous ethanol, and the solid is separated. After vacuum drying, organic nano zinc oxide is obtained. The structure of the composite antibacterial agent includes a core layer and a shell layer. The shell layer is formed by polymerizing a mixture of monomers A and B to form a cross-linked copolymer. The organic nano zinc oxide is dispersed into the shell layer and immobilized in situ. The chitosan quaternary ammonium salt is the core layer, and the lipophilic alkyl long chains of the chitosan quaternary ammonium salt form a physical entanglement with the shell layer.

2. A method for preparing a core-shell structured composite antibacterial agent as described in claim 1, characterized in that, Includes the following steps: Step 1: Add surfactant to oily solvent in proportion, water bath temperature is 40-80 ℃, stirring speed is 500-2000 rpm, stir until surfactant is fully dissolved or dispersed to obtain solvent; Step 2: Add the chitosan quaternary ammonium salt aqueous solution and organic nano zinc oxide to the oily solvent in Step 1, stir at 500-2000 rpm and water bath at 40-80 ℃ to fully emulsify the mixture and form a water-in-oil emulsion. Step 3: Transfer the water emulsion obtained in Step 2 to the dispersant aqueous solution, stir at 500-1000 rpm, and water bath at 40-80 ℃ to form a water-in-oil-in-water emulsion. Step 4: Keep the stirring speed and temperature constant, mix monomer A and monomer B evenly to form a monomer mixture, and add the monomer mixture dropwise to the emulsion obtained in step 3 at a rate of 0.1-0.2 mL / min. Start timing from the first drop of monomer mixture added. Add the initiator after 20-30 min and maintain the reaction for 1-5 h. After the reaction is completed, cool the emulsion to below 40°C. Step 5: Add a demulsifier to the emulsion in step 4 to precipitate a solid. Wash the solid with ethanol and deionized water, then dry it in a vacuum oven at low temperature or freeze-dry it to obtain a composite antibacterial agent with chitosan quaternary ammonium salt as the core layer and organic nano zinc oxide and polymer as the shell layer.

3. The method for preparing a core-shell structured composite antibacterial agent as described in claim 2, characterized in that: The degree of substitution of the chitosan quaternary ammonium salt is 40-90%, and the relative molecular mass is 50,000-800,000.

4. The method for preparing a core-shell structured composite antibacterial agent as described in claim 2, characterized in that: The solid content of the chitosan quaternary ammonium salt solution is 1-10% by weight.

5. The method for preparing a core-shell structured composite antibacterial agent as described in claim 2, characterized in that: The oily solvent is liquid paraffin and / or petroleum ether.

6. The method for preparing a core-shell structured composite antibacterial agent as described in claim 2, characterized in that: The surfactant is one or more of Span-40, Span-60, Span-80, calcium stearate and magnesium stearate.

7. The method for preparing a core-shell structured composite antibacterial agent as described in claim 2, characterized in that: The dispersant aqueous solution is a polyvinyl alcohol aqueous solution or a polyvinylpyrrolidone aqueous solution, and the mass fraction of the dispersant is 1-3%.

8. The method for preparing a core-shell structured composite antibacterial agent as described in claim 2, characterized in that: The initiator is one or a combination of two of the following: ammonium persulfate, potassium persulfate, sodium bisulfite, sodium sulfite, tetramethylethylenediamine, benzoyl peroxide, dodecyl peroxide, dicumyl peroxide, and di-tert-butyl peroxide.

Citation Information

Patent Citations

  • Polycaprolactone-based composite anti-microbial material and preparation method thereof

    CN107722578A

  • Nanometer silicon dioxide-coated quaternary ammonium salt chitosan composite antibacterial agent and preparation method thereof

    CN111838149A